CANNABIS: CURRENT GLOBAL SCENARIO AND SCOPE OF ITS MEDICINAL USE IN INDIA (Journal of Forensic Medicine & Toxicology, 2023)
Cannabis based preparations have been in used for many centuries. Over the years cannabis despite its abusive potential has emerged as one of the principal alternatives to Opioids in management of pain. Even, though cannabis cultivation and use are prohibited in many countries including India, with changing times it is essential to understand the beneficial effects of cannabis and recalibrate the policies to make the best in use of it in the field of research and development and its derivatives in the treatment of several medical conditions. Accordingly, the Government should recalibrate and amend its policies in the Narcotics Drugs and Psychotropic Substances Act (NDPS ACT) in India to facilitate research and developmental work on cannabis
Keywords: Cannabis; Government policies; Medicinal use; NDPS Ac